Exploring the Underlying Neurocognitive Correlates of Metacognitive Monitoring and Control in Authentic Digital Learning Environments - Dhanda, Kunal; Sehrawat, Sweta (Journal of Research in Vocational Education, 2025)
The corona-virus (COVID-19) pandemic had devastating impacts on not only the health and socio-economic conditions but also on the education sector in various countries. Consequently, the world of education entered a new era of learning i. e. E-learning. The management of classrooms is completely different in e-learning from the traditional learning. In traditional learning teachers has maximum control on all the classroom activities where as in E-Learning, learners should be self-disciplined and accountable for their own learning. Meta-Cognition allows people to take charge of their own learning. It involves awareness of how people learn, an evaluation of their learning needs, generating strategies to meet these needs and then implementing the strategies. Many theorists and practitioners claimed that applying meta-cognition in daily routine enhances the learning process and achievement of students. Therefore, the present paper makes an attempt to look at prospective teachers’ responses to E-learning in form of their achievement in relation to their meta-cognitive abilities. It is a descriptive study consisting sample of 40 prospective teachers from central university of Jammu selected by purposive sampling technique. For collection of data, Meta-Cognition inventory by Dr. Punita Govil (2003) and achievement scores in learning system was used. Mean, standard deviation and correlation have been used to analyze data obtained. It was found that there is significant positive relationship between responses to E-learning and meta-cognitive abilities of prospective teachers. The findings suggest that E-learning system may excel if encouragement is provided to students to use their Meta-Cognitive Abilities.